Extracorporeal Shockwave Combined with High Power Laser Therapy in the Treatment of Non-union in 5th Metatarsal Bone: A Case Report - Andayani, Ni Gusi Agung Ayu Putu Tika; Soemarjono, Arif; Soewito, Ferius (Surabaya Physical Medicine and Rehabilitation Journal, 2026)
Non-union fractures can lead to long-term physical disabilities and mental health issues. The primary treatment for long bone fractures is surgery. However, surgery may present increased perioperative risks in patients with existing comorbid conditions.  Non-surgical therapy is needed that can heal long bone fractures with minimal side effects and outcomes comparable to surgery. The aim of this report is to see the effect of GDT protocol in treating non-unions. A 44-year-old man sustained a non-union fracture in the midshaft of his left 5th metatarsal from a basketball injury. This patient underwent GDT protocol, which combines high-power laser therapy with ESWT, administered twice weekly for one month. Following two doses of GDT, the swelling reduced significantly. The Visual Analog Scale (VAS) score dropped notably after three sessions of GDT, decreasing from 8/10 to 0/10. Radiological evidence of bone healing was observed after eight sessions of GDT, confirmed by both X-ray and ultrasound imaging. Post-treatment, the patient was able to walk normally with full weight-bearing (FWB). Combining high-power laser therapy with ESWT produces a synergistic effect, improving results in this patient. There were no significant complications or adverse effects observed in patients during the GDT protocol. Further studies with larger samples and better research designs are needed to confirm this result.